Effect of Application of Soil Biological Improvement (Novel Gro Terra) and Reduction of the Amount of Npk Fertilizer on the Growth and Quality of Green Okra (Abelmoschus esculentus .L) Yield - oktavia maulani (AGRONISMA, 2022)
This study aims to determine the growth and quality of green okra plants due to the application of biological soil enhancers and a reduction in the amount of NPK fertilizer applied to the soil, as well as to determine the effect of terra application on reducing the dose of NPK fertilizer. The research was conducted at the Singosari experimental field, Soil Laboratory, Islamic University of Malang. The design used was a Randomized Block Design (RAK) with 10 treatments which were repeated 3 times and there were 120 samples of experimental plants. The application of the nevalgro terra biological enhancer showed no positive impact on the growth and quality of okra plants. O7 treatment (25% NPK fertilizer) was the best treatment as indicated by the productivity yield of 0.97 Ton/ha.